The effects of poultry meal and fishmeal on growth performance of weanling pigs - Keegan, T.P.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 210 weanling pigs (initially 16.4 lb and 21 ± 2 d of age, PIC) was used to evaluate the effects of select menhaden fishmeal and stabilized poultry meal on growth performance of nursery pigs. Five dietary treatments were fed from d 0 to 28 after weaning. Diets included a control with no specialty protein products and diets with 2.5% and 5.0% fishmeal and poultry meal replacing the lysine provide by fishmeal at 2.9% and 5.9%. All the diets were formulated on an equal lysine basis. Overall (d 0 to 28), pigs fed diets containing fishmeal had greater (P < 0.05) ADG compared to pigs fed the control diet and pigs fed diets containing poultry meal. Also, increasing fishmeal tended (quadratic, P<0.07) to improve ADG, with the greatest increase observed in pigs fed 2.5% fishmeal. Feed intake was not affected by any dietary treatment. Pigs fed diets containing select menhaden fishmeal had improved (P<0.05) feed efficiency compared to pigs fed diets containing stabilized poultry meal. In conclusion, the addition of fishmeal to the diet improved the growth performance of weanling pigs, while stabilized poultry protein meal did not affect growth performance.
Keywords: Poultry meal; Weanling pigs; Fishmeal; Swine